Kajian Ergonomi Pada Display Statis (Penunjuk Informasi) di Perpustakaan Universitas Bina Darma - Aisyah Wahyu Kusuma Ningrum; Herlina Herlina (Institut Agama Islam Negeri (IAIN) Curup, 2023)
The purpose of this study to find out what forms of static displays (information pointers) are provided by the Bina Darma University Library which are then studied in terms of ergonomics based on the value of comfort, beauty, and usefulness. The type of research used descriptive qualitative research. Determination of informants is determined based on non-probability techniques, namely by using purposive sampling. The informants selected were one person in the library staff, namely the librarian. The data collection technique through interviews which are then processed so that they can find conclusions/verification results. The results obtained are static displays in the Bina Darma University Library, namely Warning Displays, working hours, library labels, instructions for using turnitin, instructions on collections, suggestion box labels, and instructions for opening doors. The static display in the Bina Darma University library is still minimal. This is due to the lack of information related to library rules, organizational structures and so on, making users confused and preferring to ask the librarian